1994
DOI: 10.1007/bf00039544
|View full text |Cite
|
Sign up to set email alerts
|

Induction of chilling resistance by water stress, and cDNA sequence analysis and expression of water stress-regulated genes in rice

Abstract: Exposure of seedlings of a chilling-sensitive variety of rice (Oryza sativa L. cv. Wasetoittu) to water stress (0.5 M mannitol, 30 min) at room temperature induced a degree of chilling resistance. No such resistance was induced by exogenous abscisic acid (ABA) application (10 microM, 60 min). Upon short-term water stress, new transcripts were expressed in both seedlings and suspension-cultured cells. We suggest that the genes induced by short-term water stress, and not those induced by ABA, are related to acqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0
2

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(80 citation statements)
references
References 59 publications
3
75
0
2
Order By: Relevance
“…These results extend preliminary experiments on two new classes of lipoxygenase genes isolated from soybeans in different developmental stages [23]. Abscisic acid is generally reported to mediate the plant response to water deficit [25], although such mediation does not always occur [26]. Here, it is shown that osmotic stress enhances LOX-I and -2 expression without the intermediacy of ABA.…”
Section: Discussionsupporting
confidence: 85%
“…These results extend preliminary experiments on two new classes of lipoxygenase genes isolated from soybeans in different developmental stages [23]. Abscisic acid is generally reported to mediate the plant response to water deficit [25], although such mediation does not always occur [26]. Here, it is shown that osmotic stress enhances LOX-I and -2 expression without the intermediacy of ABA.…”
Section: Discussionsupporting
confidence: 85%
“…The two full-length cDNAs share 72% identity, the ORFs are 78% identical, and the translated amino acid sequences are 83% identical. The deduced amino acid sequences of VpGAS1 and VpGAS2 are highly homologous to known GAS genes from Arabidopsis thaliana (15), Ajuga reptans (16), tomato (17), rice (18), zucchini (19), and soybean (19). Highest amino acid homology (87%) is with the gene from A. reptans, which is most closely related to V. phoeniceum.…”
Section: Resultsmentioning
confidence: 99%
“…1A). Among these genes, we found five well-known rice stress-inducible genes: Asr1, LIP9, OsNAC6, salT, and WSI724 (Aguan et al, 1991;Takahashi et al, 1994;Garcia et al, 1998;Vaidyanathan et al, 1999;Kikuchi et al, 2000). Rice cDNA clones JRC (JIRCAS Rice cDNA clone) 0549, JRC0712, JRC0835, AU068246, and C28206 that encode Glycoside hydrolase; pyruvate dehydrogenase kinase 1; Zeaxanthin epoxidase; OsABA2; Papain Cys protease; and UDP-Gal-4-epimerase, respectively, and five cDNAs (JRC0297, JRC0710, JRC2563, JRC1110, and JRC1142), whose function is unknown, were also included in this group.…”
Section: Relationship Between Each Stressmentioning
confidence: 99%